Investigation of Ketotifen Fumarate in Pharmaceuticals Using Iron (III) Chloride and Two Chelating Agents – Spectrophotometerically - P., K. Asha; M.S. , Raghu; V.S., Anusuya Devi (International Journal of Psychosocial Rehabilitation, 2020)
Spectrophotometric methods for the drug ketotifen fumarate (KTF) have been developed and validated both for bulk drug and its tablets by two simple, selective methods. This involves oxidation of KTF with ferric chloride in a neutral medium and successive chelation of the resulting iron (II) with 1, 10-phenanthroline (phen) (Method A) or 2, 2΄-bipyridyl (bipy) (Method B). The resultant red-colored chromogens are measured at 510 for method A and 520 nm for method B. Beer’s law is obeyed in the concentration ranges of 0.4-8.0 and 1-25 μg ml⁻¹ with molar absorptivity values of 5.35 x 10⁴ and 0.789 x 10⁴ l mol⁻¹cm⁻¹ and Sandell sensitivities of 0.008 and 0.055 μg cm⁻² for method A and method B, respectively. The limits of detection and quantification are also stated. For the present paper, the proposed methods were applied for the determination of KTF. There was a good comparison of the results for proposed procedures and the reference method; there was not much difference in accuracy and precision.